Limiting Outer Space Astroculture After Apollo (Palgrave Studies in the History of Science and Technology, 2018)
Limiting Outer Space propels the historicization of outer space by focusing on the Post-Apollo period. After the Apollo moon landings, disillusionment set in. With the return of the last astronaut in 1972, the skies - rather than the distant stars - once again became the limit. No longer considered the inevitable destination of human expansion, outer space lost much of the popular appeal, cultural significance and political urgency that it had gained since the end of the Second World War. With the rapid waning of the worldwide Apollo frenzy, the optimism of the Space Age gave way to an era of planetized limits. Bringing together the history of European astroculture and American-Soviet spaceflight with recent scholarship on the 1970s, the thirteen chapters in this cutting-edge volume examine the reconfiguration of space imaginaries from a multiplicity of disciplinary perspectives. Rather than invoking oft-repeated narratives of Cold War rivalry and an escalating Space Race between East and West, Limiting Outer Space breaks new ground by exploring a hitherto underrated and understudied decade, the Post-Apollo period.